Could everyday technology improve access to assessments? A pilot study on the feasibility of screening cognition in people with Parkinson's disease using the Montreal Cognitive Assessment via Internet videoconferencing. (5th April 2016) - Stillerova, Tereza; Liddle, Jacki; Gustafsson, Louise; Lamont, Robyn; Silburn, Peter
Abstract : Background: The distances and distribution of people, and pressures on the health system in Australia mean that access to services for people living with a neurodegenerative condition may be inadequate. Telehealth may offer ways to provide timely and efficient monitoring and support. People with Parkinson's disease require regular screening of their symptoms and needs, but may have limited access to health professionals. Cognitive changes can impact on occupational performance, thus timely monitoring of cognition is important for informing occupational therapy interventions. Aim: To evaluate the feasibility of screening cognition in people with Parkinson's disease using available technology in their homes. Method: Eleven participants with Parkinson's disease completed the Montreal Cognitive Assessment face‐to‐face and then via videoconferencing one week later using the technology available at their home. Participants and assessors provided feedback on their experience. Results: All Montreal Cognitive Assessment items could be completed over videoconference (e.g. Skype), with a median difference of 2 (IQR: 1–2.5) between face‐to‐face and videoconference scores. Higher scores were not favoured by either mode of assessment. Three participants received inconsistent cognitive classifications between the two assessment methods. Participant and assessor feedback indicated reported benefits including convenience as well as technological limitations. Conclusions: Given the pressures on the health system and the apparent acceptability to consumers, occupational therapists may explore the utility of readily accessible technology to enable timely monitoring of cognition for people with Parkinson's disease. Further research is needed to develop and demonstrate the reliability and validity of this approach.